Situational eLearning : A Crowdsourcing Approach to the Definition and Assessment of Key Practice-Ready Academic Outcomes : Final Report. - Newton, Sidney; Lowe, Russell; Pickersgill, Sean; Hardie, Mary; Srivastava, Amit; Rameezdeen, Rameez; Zillante, George (Office for Learning and Teaching, 2017)
Australia must do more to develop graduates with the practice-ready skills they need to play an effective role in the workplace. Situated learning lends itself to the development of key practice-ready skills, but it is contingent on the availability of authentic clinical experiences. The potential for replacing direct student engagement in practice with a computer-simulated clinical experience is apparent. This is the final report from a project that addressed the potential for emerging virtual reality and related digital technologies to provide and assess particular clinical experiences. The project delivered three learning and teaching resource outcomes: The Situation Engine which uses video game technologies to model and manage practical situations; an open access, online database of learning and teaching resources in construction technology; and a Moodle resource that binds learning resources to specific construction technology learning outcomes.